A prospective study on the effect of topical lidocaine gel versus drops on ocular pain in manual small incision cataract surgery - Krishnan, Prakash; Kuriachan, Sanitha; Sethuraman, Nirmala (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Cataract is globally acknowledged leading cause of blindness. This study was undertaken to compare the effects of Lidocaine 4% drops with 2% gel on intra operative and post-operative pain in patients who underwent manual small incision cataract surgery. Methods: It was a single Centre, one-surgeon, prospective, comparison study. Patients enrolled for surgeries were divided into Group A: Lidocaine 4% drops 1 ml was instilled in the conjunctival sac 5 minutes before surgery and Group B: Lidocaine 2% gel 2ml was applied. Endpoints evaluated were ocular pain of patient during and after surgery. Results: A total of 60 patients underwent MSICS, out of which 30 each received drops and gel. Mean intraoperative pain VAS score was 2.26±0.69 for gel group and 5.13±1.13 for drops group (p*<0.001) Mean post-operative pain VAS score was 0.26±0.69 in gel group and 1.13±1.13 in drops group (p*=0.002). Conclusions: Compared to drops, Lidocaine gel has reduced intraoperative and post-operative pain.